A Modular Approach to Animation of Simulation Models - Bardohl, R.; Ermel, C.; Ribeiro, L. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2000: Anais do XIV Simpósio Brasileiro de Engenharia de Software, 2000)
The use of simulation within software development has as main aims to validate the system, as well as to recognize performance aspects. A simulation model includes the description of the behavior of the systems, but also intended animation strategies (to visualize the simulation) and statistics collecting/evaluating procedures. In this paper we present a modular approach for animating simulation models. Both the system's behavior and its animation are modeled by graph grammars, a formal, yet intuitive visual specification technique. The simulation of the system as well as its animation are supported by tools. We discuss the integration of the tools PLATUS, designed to construct the simulation models, and the tool GENGED, designed for the development of visual languages, in order to obtain an environment in which animation modules can be obtained (from GenGED) and used (in PLATUS). Moreover, due to the modular structure, animation can be exchanged easily, and can be also reused by other simulation models.